DIPG-44. A GAIN OF FUNCTION Ezh2 MUTATION DELAYS DIFFUSE INTRINSIC PONTINE GLIOMA PROGRESSION. (4th December 2020) - Dhar, Swati; Gadd, Samantha; Brat, Daniel; Becher, Oren
Abstract: BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) remains an incurable pediatric brain cancer. The oncohistone H3K27M implicated in 80% of the cases, is also predicted to target Enhancer of Zeste Homolog 2 (Ezh2), the catalytic component of the Polycomb Repressor Complex 2 (PRC2). There are no reported mutations of Ezh2 and its function in DIPG is not fully determined. This work aims to address the role of Ezh2 in DIPG. METHODS: Brainstem tumors were established by intracranial injections of Nestin ;Tv-a; Ezh2 Y641F/+ (NTv-a; Ezh2 Y641F/+ ) neonatal pups using Replication Competent Avian Sarcoma leucosis virus long terminal repeat with splice acceptor (RCAS) viruses, expressing PDGF-B, p53 shRNA, and RCAS-CRE/Y. Immunohistochemical staining for Ki-67 and H3K27me3 were performed on the Discovery ULTRA (Ventana). RESULTS: Ezh2 overexpression ( Ezh2 Y641F/+, RCAS CRE ) conferred a survival advantage of approximately 10 days (n=20 mice/group, p<0.001). H3K27me3 levels were significantly upregulated in RCAS CRE group (50% vs 20% in RCAS Y, n=4 tumors/group, p<0.03), with a concomitant lower Ki-67 staining (30% vs. 55% in RCAS Y, n=3 tumors/group, p<0.05). Interestingly, pathological review categorized more RCAS-CRE tumors as 'atypical'. RNA-sequencing of virus-infected neural precursor cells revealed a suppression of inflammatory/interferon gene signature in the Ezh2 overexpression group. CONCLUSIONS AND FUTURE DIRECTIONS: Enhanced Ezh2 activity appears to delay DIPG pathogenesis. Ongoing work aims to highlight the contribution of differentially expressed gene signatures that contribute to this phenotype.